Artificial Intelligence over Infrared Images for Medical Applications and Medical Image Assisted Biomarker Discovery First MICCAI Workshop, AIIIMA 2022, and First MICCAI Workshop, MIABID 2022, Held in Conjunction with MICCAI 2022, Singapore, September 18 and 22, 2022, Proceedings - Kakileti, Siva Teja.; Gabrani, Maria; Manjunath, Geetha; Rosen-Zvi, Michal; Braman, Nathaniel; Schwartz, Robert G.; Frangi, Alejandro F.; Chung, Pau-Choo.; Weight, Christopher; Jagadish, Vekataraman (Cham : Springer Nature Switzerland : Imprint: Springer, 2022)
This book constitutes the refereed proceedings of the First Workshop on Artificial Intelligence over Infrared Images for Medical Applications, AIIIMA 2022, and the First Workshop on Medical Image Assisted Biomarker Discovery, MIABID 2022, both held in conjunction with MICCAI 2022, Singapore, during September 18 and 22, 2022. For MIABID 2022, 7 papers from 10 submissions were accepted for publication. This workshop created a forum to discuss this specific sub-topic at MICCAI and promote this novel area of research among the research community that has the potential to hugely impact our society. For AIIIMA 2022, 10 papers from 15 submissions were accepted for publication. The first workshop on AIIIMA aimed to create a forum to discuss this specific sub-topic of AI over Infrared Images for Medical Applications at MICCAI and promote this novel area of research that has the potential to hugely impact our society, among the research community.
Keywords: Image processing-Digital techniques; Computer vision; Machine learning; Education-Data processing; Social sciences-Data processing; Computer Imaging, Vision, Pattern Recognition and Graphics; Machine Learning; Computers and Education; Computer Application in Social and Behavioral Sciences